1. implicit differenitaion

so the problem asks us to solve for $\frac{d^2y}{dx^2}$ from the equation
$x^5+y^5=4$

I found $\frac{dy}{dx}=\frac{(-5x^4)}{(5y^4)}$, how would I go about solving for $\frac{d^2y}{dx^2}$?

2. Originally Posted by ascendancy523
so the problem asks us to solve for $\frac{d^2y}{dx^2}$ from the equation
$x^5+y^5=4$

I found $\frac{dy}{dx}=\frac{(-5x^4)}{(5y^4)}$, how would I go about solving for $\frac{d^2y}{dx^2}$?
Cancel 5 to make things easier, then use the quotient rule

I get
$\frac{4x^3(y-x)}{y^5}$

3. Originally Posted by ascendancy523
so the problem asks us to solve for $\frac{d^2y}{dx^2}$ from the equation
$x^5+y^5=4$

I found $\frac{dy}{dx}=\frac{(-5x^4)}{(5y^4)}$, how would I go about solving for $\frac{d^2y}{dx^2}$?
I get ...

$\frac{d^2y}{dx^2} = - \frac{16x^3}{y^9}$

4. Originally Posted by skeeter
I get ...

$\frac{d^2y}{dx^2} = - \frac{16x^3}{y^9}$
I got a different answer from both of you but I typed in $\frac{d^2y}{dx^2} = - \frac{16x^3}{y^9}$ and it was right. How did you go about solving it?